Le Service Anti-Crime des Assureurs - Cloutier, Jean-Claude (Assurances, 1995)
The Bureau has two main objectives: to prevent insurance crime by providing underwriters with loss information that will help evaluate poor risks; to help claims personnel and independent adjusters discover attempted fraud before settlements are paid, or alternatively, identify legitimate daims quickly so that payment may be made.